That time I got drunk and yeeted a love potion at a werewolf - Lemming, Kimberly (Lemming, Kimberly. Mead mishaps, 2024)
"Brie's never been particularly coordinated...or lucky. Who else would accidentally throw a drink at someone's head only to miss entirely and hit a stranger behind them? And who else would have that stranger fall madly in love with them because it turns out that the drink she threw was a love potion? Yeah, probably just Brie.... Running her cheese business and dealing with a pirate ship full of demons that just moved into town was hard enough. Now on top of it, she has to convince a werewolf that she's not really his fated mate. Though even she's got to admit...having a gorgeous man show up and do all her chores while telling her she's beautiful isn't the worst thing to happen to a girl."--